The Geographies of International Student Mobility Spaces, Places and Decision-Making - Beech, Suzanne E.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book offers critical insights into the geographies of the international student higher education experience from initial recruitment, through to the plethora of personal factors which influence their decisions to become mobile and experiences when abroad. From the student perspective these include, but are not limited to, the importance of social networks, desire for a multicultural experience and the attraction to certain locations as discussed in this volume. However, unlike other work, it also reflects on the motivations of the HEIs themselves and their need to continue recruiting students in the face of greater competition from overseas. Recognising this omission, this book also analyses the resulting migration industries and how these are sustained (and even necessitated) by the sector. It is, therefore, the first to bring together these wider institutional narratives with those of the students resulting in a holistic and comprehensive insight into the student mobility process.
Chapter 1: Introduction - Conceptualising the International Student -- Chapter 2: Recruiting Students - Negotiating Policy -- Chapter 3: Recruiting Students - Developing Migration Industries -- Chapter 4: Why Study Overseas? Identifying Instrumental Factors in Student Mobility -- Chapter 5: Reputation, Rankings and the Russell Group - What Makes an Excellent University? -- Chapter 6: Friendship and Kinship - Driving Mobility -- Chapter 7: Understanding Place - Imaginative Geographies and International Student Mobility -- Chapter 8: Writing Biographies, Travel and a Multicultural Experience? -- Chapter 9: Conclusion - Developing a Theoretical Framework of International Student Mobility.
Keywords: Human geography; Emigration and immigration; Educational sociology; Human Geography; Human Migration; Sociology of Education